2018
DOI: 10.21037/jtd.2018.10.89
|View full text |Cite
|
Sign up to set email alerts
|

Total endoscopic repair of atrial septal defect under on-pump beating heart

Abstract: Background: We previously reported the techniques for total endoscopic atrial septal defect (ASD) repair on hearts arrested with cardioplegia through three small incisions in the chest wall without aid of a surgical robotic system. The optimal results motivated us to use total thoracoscopic technology for ASD on perfused beating hearts. Methods: From 2010 to 2017, 161 patients with a mean age of 28.31±12.34 years who underwent nonrobotically assisted total thoracoscopic closure for ASD were included in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 16 publications
2
12
0
1
Order By: Relevance
“…Atrial septal defect (ASD) is the most common congenital heart disease (CHD) of adulthood [ 1 ], accounting for about 30–40% of adult CHD [ 2 , 3 ]. The 2008 ACC/AHA and 2010 ESC guidelines for the management of adult CHD recommended that atrial septal defect repair should be performed either surgically or percutaneously if right atrial and ventricular enlargement occur, regardless of symptoms [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atrial septal defect (ASD) is the most common congenital heart disease (CHD) of adulthood [ 1 ], accounting for about 30–40% of adult CHD [ 2 , 3 ]. The 2008 ACC/AHA and 2010 ESC guidelines for the management of adult CHD recommended that atrial septal defect repair should be performed either surgically or percutaneously if right atrial and ventricular enlargement occur, regardless of symptoms [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 This phenomenon is most often recorded in young women and small children, who often have small FAs associated with a strong spasm reflex of the vascular smooth muscle. 15 The weight limit was ≥13.5 kg, 7 ≥15 kg, 16 or >20 kg 17 depending on the studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, these previous studies were on adult VSD patients, and they did not compare the effect of the two techniques on postoperative ICU stay, length of hospital stay, inpatient complications, and shortterm and medium-term outcomes. In this context, Tang et al compared the on beating heart and cardioplegic techniques in the repair of atrial septal defects (ASDs) and found that the durations of surgery, CPB, aortic cross-clamp, mechanical ventilation, ICU stay, and postoperative hospital stay were all markedly shorter in the on beating heart group (P<0.05) and no severe complications occurred (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that repairing a VSD on a beating heart is an effective strategy for avoiding CAVB (12,16). Air embolism remains a significant concern in the repair of septal defects on a beating heart (10); however, previous studies have reported that opening the beating left ventricle does not necessarily increase the risk of air embolism (12,21,25). In light of this evidence, routine measures were applied in the present study to prevent air intake to the left ventricle, and continuous monitoring of TEE showed no significant air volume in the left ventricle.…”
Section: Discussionmentioning
confidence: 99%